Synthesis and Biophysical Study of Disassembling Nanohybrid Bioconjugates with a Cubic Octasilsesquioxane Core - Trastoy Bello, Beatriz; Bonsor, Daniel A; Perez-Ojeda Rodriguez, Maria Eugenia; Jimeno, Maria Luisa; Mendez-Ardoy, Alejandro; Fernandez, JMG; Sundberg, Eric J; Chiara, Jose Luis (Advanced Functional Materials, 2012)
Polyhedral oligosilsesquioxanes (POSS) have recently attracted attention as scaffolds for the synthesis of multivalent bioconjugates. The synthesis of glycosyl-octasilsesquioxanes (glyco-POSS) using a copper(I)-catalyzed azide-alkyne 1,3-dipolar cycloaddition approach is reported. The problems associated with the use of bases or aqueous media in their preparation are investigated and a comprehensive study of the multivalent interaction between the mannosyl-octasilsesquioxanes and a model lectin, concanavalin A (Con A), using an array of complementary biophysical techniques is presented. The possibility to modulate the half-life of POSS conjugates in aqueous solution and the low toxicity of their constituent monomeric organosilanes offers an advantage over other scaffolds in vivo, preventing bioaccumulation and saturation of complementary receptors (lectins). Despite the hydrolysis in water, the octamannosyl-POSS studied shows a 50-fold higher binding affinity to Con A than methyl a-D-mannopyranoside. These experiments suggest that the novel glyco-POSS are attractive compounds for in vivo applications that require multivalent display of glycans.
Keywords: hybrid materials; biomimetics; silsesquioxanes; carbohydrates; click chemistry